Monte Carlo simulations of the critical properties of the restricted primitive model - Caillol, J.-M. (Condensed Matter Physics, 2004)
Recent Monte Carlo simulations of the critical point of the restricted primitive model for ionic solutions are reported. Only the continuum version of the model is considered. A finite size scaling analysis based in the BruceWilding procedure gives critical exponents in agreement with those of the three-dimensional Ising universality class. An anomaly in the scaling of the specific heat with system size is pointed out.